Perilaku Sosialita Memamerkan Status melalui Barang Branded dan Brand Prominance - Purwanto, Purwanto; Manafe, Leonard Adrie; Fatchurrohman, Mochamad (Universitas Batanghari Jambi, 2024)
The purpose of the present study was to explore the relationship between consumer motives mediated by the choice of brand prominence and the behavior of purchasing counterfeit products in three groups/classes of consumers (patrician, parvenus and poseur) of luxury fashion brands. Data were obtained from a sample consisting of 230 respondents who were considered eligible. Three findings are obtained. First, for the poseur, consumer motives for purchasing products are positively related to counterfeit products and conspicuous brand prominence. Second, for the parvenus, the consumer motives are not related to counterfeit products, but it is related to conspicuous brand prominence. Third, for the patrician, consumer motives for purchasing products are not related to counterfeit products and inconspicuous brand prominence.